2017
DOI: 10.1111/his.13251
|View full text |Cite
|
Sign up to set email alerts
|

EGFR gene mutation in gastrointestinal stromal tumours

Abstract: We first established that GISTs carrying EGFR mutation are relatively benign tumours. Although EGFR mutations were rarely present in GIST, EGFR seems to play a significant role in the development and progression of GIST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
3
9
0
1
Order By: Relevance
“…Among these mutations, D770_N771insG and T790M occurred together with KIT , NRAS , or AKT1 mutations, whereas only the S752I/F mutation was harbored by KIT / PDGFRA WT GISTs. This result may overturn the hypothesis of Shi et al 19 that EGFR mutations are mutually exclusive with KIT , PDGFRA , KRAS , or BRAF mutations in primary GISTs. In addition, the EGFR mutation frequency detected in our study is higher compared with previous reports.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Among these mutations, D770_N771insG and T790M occurred together with KIT , NRAS , or AKT1 mutations, whereas only the S752I/F mutation was harbored by KIT / PDGFRA WT GISTs. This result may overturn the hypothesis of Shi et al 19 that EGFR mutations are mutually exclusive with KIT , PDGFRA , KRAS , or BRAF mutations in primary GISTs. In addition, the EGFR mutation frequency detected in our study is higher compared with previous reports.…”
Section: Discussionsupporting
confidence: 57%
“… 18 However, there are very few literature on EGFR mutation in GISTs. 19 In the present study, 4 EGFR mutations (D770_N771insG, T790M, and S752I/F) were detected among the 40 GISTs. Among these mutations, D770_N771insG and T790M occurred together with KIT , NRAS , or AKT1 mutations, whereas only the S752I/F mutation was harbored by KIT / PDGFRA WT GISTs.…”
Section: Discussionsupporting
confidence: 46%
“…58 Additional genetic categories subsequently emerged, including succinate dehydrogenase (SDH)deficient GIST, 59,60 GIST with bi-allelic NF1 inactivation 61 and BRAF V600E-mutant GIST. 62,63 Exceptionally rare genetic alterations have also been reported, including EGFR mutations 64 and FGFR1, NTRK3 65 and ALK gene fusions. 66 Some genetic subtypes have predilections for particular locations within the gastrointestinal tract: for example, NF1-inactivated GIST occurs almost exclusively in the small intestine, while SDH-deficient GIST occurs almost exclusively in the stomach.…”
Section: Gastrointestinal Stromal Tumoursmentioning
confidence: 99%
“…In addition to the mutations in well-known key driver genes, including KIT and PDGFRA, recent studies have revealed genetic alterations of other tumor-related genes in GISTs. For instance, EGFR mutations are found in 0.93% (3/323) of primary GISTs, and do not overlap with mutations in KIT, PDGFRA, KRAS or BRAF (89). EGFR mutations are associated with a stomach location, female gender and low recurrence rate.…”
Section: Other Gene Mutations In Gistmentioning
confidence: 99%